Effect of galactomannan (Caesalpinea pulcherrima) on different fi sh restructuring methods - Lima Sousa, Sanyelle (Revista Ciência Agronômica, 2021)
Restructuring consists of aggregating small food parts with the addition of binding agents which, after mold pressing will undergo a gel confi guration stage using hot or cold methods. This work aims to evaluate the effect of galactomannan from Caesalpinea pulcherrima as a binding agent, in a restructured fi sh product obtained from the meat of tibiro - Maracaibo leatherjacket (Oligoplites palometa) by hot and cold restructuring methods, comparing it with a restructured control made with transglutaminase, regarding the physicochemical and mechanical characteristics. The restructured product elaborated with galactomannan using the cold method denoted better water retention capacity, also registering the smallest weight loss values of cooking in the two restructuring methods. The results obtained from the mechanical properties of texture such as hardness and cohesiveness of the product restructured with galactomannan using the cold method were similar to those of the control sample. Furthermore, the addition of galactomannan by the hot method provided closer similarity with the control sample, resulting in better softness, lower adhesiveness, and elasticity. The restructured product elaborated by the cold method with galactomannan from C. pulcherrima revealed better physicochemical characteristics; the mechanical properties exhibited an analogy with the restructured product using transglutaminase; hence, it can be indicated as a binding agent in the elaboration of this type of product.